Using Pedagogic Intervention to Cultivate Contextual Lexical Competence in L2 An Investigation of Chinese EFL Learners - Wang, Gaiyan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book challenges prevailing linguistic presumptions concerning contextual lexical meaning by determining whether pedagogic intervention targeted at raising Chinese EFL learners' awareness of the pragmatic nature of contextual lexical meaning can enhance the learners' contextual lexical inferencing competence (CLIC). CLIC is crucial to the development of their vocabulary, reading ability and autonomy in reading. Through an empirical study conducted among a group of adult Chinese students of English, the author shows that the power of CLIC instruction lies mainly in its effectiveness in enhancing learners' self-confidence in making lexical inferences. This book will be of interest to researchers and students of applied linguistics, TESOL and language education more generally, and for language professionals keen to extend their research experience. Wang Gaiyan is a professor at Xi'an International Studies University, China. She obtained her Ph.D. in applied linguistics from Guangdong University of Foreign Studies, Guangzhou, China. Her research interests lie mainly in second language acquisition and pedagogy, including second language vocabulary acquisition in reading process, the nature of lexical meaning, and second language vocabulary pedagogy. The focus of her research is on incidental vocabulary acquisition in reading contexts.
Chapter 1: Introduction -- Part One: CLIC: The Concept and Cultivation -- Chapter 2: Introduction: What is CLIC? -- Chapter 3: CLIC-Related Concepts & A CLIC Conceptual Model -- Chapter 4: In Search of Theoretical Foundations for CLIC Instructional Methods -- Part Two: A Pedagogical Experiment on CLIC Cultivation -- Chapter 5: Empirical Research Methodology -- Chapter 6: Preparation of the Data -- Chapter 7: Effects of Pedagogical Intervention -- Part Three: Further Thoughts on CLIC Pedagogy -- Chapter 8: CLIC Pedagogy: Reflections.
Keywords: Applied linguistics; Language and languages -- Study and teaching; Lexicology; Asia -- Languages; Applied Linguistics; Language Teaching and Learning; Lexicolopgy / Vocabulary; Language Education; Asian Languages